The development and validation of the assessment engagement scale - Evans, Carol; Zhu, Xiaotong (Frontiers in Psychology, 2023)
The quality of student engagement in assessment within higher education affects learning outcomes. However, variations in conceptions of what quality in engagement looks like impacts assessment design and the way that students and lecturers engage with each other in the assessment process. Given that assessment is an important driver of student engagement in higher education, it is surprising that no specific measures to support understanding of this measure exist. To address this significant gap, we outline the evolution of an assessment engagement scale derived from a research-informed conceptual framework utilising best practice in assessment and feedback. We consider the validity and utility of the scale in supporting students’ understanding of assessment and their role within it. Exploratory and confirmatory factor analyses confirmed the nine-item scale’s underpinning factors to include (i) Understanding of the Assessment Context (UAC) including one’s role within it, and confidence in navigating assessment requirement, and (ii) Realising Engagement Opportunities (REO) (i.e., willingness to engage and ability to utilise the assessment context effectively to support one’s understanding). Implications for assessment practices in higher education are discussed, along with the potential of the scale as a predictive and developmental tool to support enhancements in assessment design and student learning outcomes.